EXPERIMENTAL INVESTIGATION OF POLYMER CONCRETE AND FIBER REINFORCED CONCRETE WITH CONVENTIONAL CONCRETE - Azhagumathi, S.; Suresh, R. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In this project is planned to compare two different high strength concrete, one is made up of polymer and another one is made up of steel fiber. In polymer concrete, unsaturated isopthalic polyester(9%,12%,15%,18%) along with a catalyst cobalt octate(1%) and a accelerator methyl ethyl ketone peroxide(1%). In fiber reinforced concrete, binding wire of 1 cm long is going to be used as steel fiber(1%,1.5%,2%,2.5%). Using the above concrete, appreciable number cube, cylinders and prisms are going to be made and they will test for compressive and tensile strength respectively. The test results are going to be compared with conventional concrete from the comparisons the effectiveness of the high strength concrete will be evaluated.